The effect of using kinetic rhythm on the level of skill performance and the digital achievement of javelin throwing effectiveness for youth - William, W. L. (Journal of Human Sport & Exercise, 2021)
The trainer's knowledge of the kinetic rhythm well gives him an advantage in the ability to objectively evaluate the level of performance and stand on the strengths and weaknesses of that performance, Thus, it is easy for him to direct and modify the course of training to serve the level of mastery of movement technicality and improve the physical abilities of that event or sports skill by distributing the strength ratios to each part of the movement and in proportion to the importance of each part of the movement which represents the effective dynamic dimension of the movement. the kinetic rhythm ultimately means the balance of the parts of the movement in terms of the forces exerted at the specified times. The researcher used the experimental approach with a dual design using the pre-post measurement of two equivalent groups, one control and the other experimental. The researcher reached the following conclusions. The rhythm creates an optimal exchange between contraction and extension in the muscles, making the performance economical for the energy expended. The rhythm works to delay the appearance of fatigue on the players and therefore because contraction and extension help to speed up blood circulation and this means supplying the muscles with the oxygen and energy needed to perform the movement. The correct rhythm of the movement increases the level of performance and it helps the player move his body parts in the correct path of movement and the rhythm of the movement helps in identifying the parts of the movement that need a higher rate of strength.